Concordance of chlamydia trachomatis infections within sexual partnerships. Issue 1 (2nd October 2007) - Rogers, S M; Miller, W C; Turner, C F; Ellen, J; Zenilman, J; Rothman, R; Villarroel, M A; Al-Tayyib, A; Leone, P; Gaydos, C; Ganapathi, L; Hobbs, M; et al.
Abstract : Objectives: The enhanced sensitivity of nucleic acid amplification tests (NAAT) provides an opportunity for estimating the prevalence of untreated Chlamydia trachomatis infections. The transmissibility and public health significance of some NAAT-identified infections are, however, not known. Methods: Adults attending an urban emergency department provided specimens for C trachomatis screening using NAAT. Participants testing positive were offered follow-up including re-testing for C trachomatis using NAAT and traditional methods, eg culture and direct fluorescent antibody, and were treated. Partners were offered identical evaluation and treatment. Overall, 90 C trachomatis -positive participants had one or more sexual partners enrolled. Results: Evidence of transmission, as defined by infection concordance between partnerships, was observed among 75% of partners of index cases testing positive by both NAAT and traditional assay but only 45% of partners of index cases testing positive by NAAT only (prevalence ratio 1.7, 95% CI 1.1 to 2.5). Among index participants returning for follow-up, 17% had no evidence of C trachomatis infection by NAAT or traditional assay (median follow-up three weeks). Conclusions: A substantial proportion of positive NAAT results for chlamydial infection may be of lower transmissibility and may not persist after a short follow-up. The long-term health effects of some positive NAAT are uncertain.